De orfebres, fenicios e indígenas: la nueva inscripción sobre molde de joyería del Castillo de Doña Blanca (Puerto de Santa María, Cádiz) y el conocido grafito bilítero del Cabezo de San Pedro (Huelva) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A goldsmith mold with a brief Phoenician inscription (composed of just two letters) was found in the archaeological site of “Castillo de Doña Blanca” (El Puerto de Santa María, Cádiz) among artefacts which date to the first half of the 7th century B. C. The author of the inscription could have been a literate craftsman, skilled both in engraving and in writing. The reading of this new inscription is surprisingly the same as the reading in Phoenician of a famous graffito found in the city of Huelva. As the nature and interpretation of this graffito are still the subject of discussion and controversy, the study takes into account the new inscription from Doña Blanca in order to shed light on both the documents.
Keywords: Epigraphy; Writings; Language; Phoenicians; Palaeohispanical Peoples